Interactive Teaching Materials Based on Character Education to Improve English Reading Comprehension of Elementary School Students - Ni Putu Artila Dewi; Ni Made Dita Sintadewi; Tiara Kusuma Dewi (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the low reading comprehension of English among grade IV elementary school students and the need for interactive teaching materials that not only improve academic ability, but also students' character. This study aims to develop and test the effectiveness of interactive teaching materials based on character education to improve students' reading comprehension. The research uses the Research and Development (R&D) method with the research subject of grade IV elementary school students. The instruments used include observation sheets, expert assessments of the content and structure of teaching materials, and questionnaires to get feedback from teachers and students. Data was collected through classroom observations, expert assessments, and interviews. The data was analyzed using descriptive analysis to determine the effectiveness of teaching materials. The results of the study show that interactive teaching materials, consisting of digital games, stories, and quizzes, can significantly improve students' reading comprehension and increase their learning engagement. In addition, the integration of character education in this teaching material promotes positive attitudes and behaviors in students. The implication of this study is that character education-based interactive teaching materials are effective in improving reading skills, and need to be applied to other subjects with continuous teacher training for optimal results.